The Potential Development of Android-Based Lesson Study in Mathematics Learning at Junior High Schools - Anita Dewi Utami; Rofiki, Imam; Suwarman, Ramdhan Fazrianto; Listiawan, Tomi; Manunggal, Deddy Trisna; Dyaswardani, Hapsari; Akmalia, Yuyun (IKIP PGRI Bojonegoro, 2025)
Mathematics learning in junior high schools often faces challenges such as low conceptual understanding and limited teacher collaboration. Android-based Lesson Study (LS) offers a promising solution through technology integration, but related research is still scarce. This study analyzes the potential of Android-based LS for mathematics learning in junior high schools based on Scopus-indexed literature. A systematic literature review (SLR) was conducted using the PRISMA protocol. Searches in Scopus used the keywords